Investigating the role of biophilic design to enhance comfort in residential spaces: human physiological response in immersive virtual environment - Al Sayyed, Heba; Al-Azhari, Wael (Frontiers in Virtual Reality, 2025)
Indoor environments significantly impact human health. The COVID-19 pandemic highlighted the urgency of reconnecting with nature to maintain both physiological and psychological health. Modern indoor lifestyles have increased isolation from nature, diminishing these benefits. While previous studies have demonstrated the positive effects of biophilic design on human physiological comfort, its application in residential spaces remains underexplored. This study investigates how biophilic design elements—including natural light, ventilation, and greenery—influence physiological stress and comfort in residential settings using immersive virtual environments (IVE). Ninety-four participants were exposed to two test environments: one with biophilic elements and one without. Measurements of skin conductance level (SCL) and blood pressure (BP) were recorded across three phases: relaxation, exposure to mild stressors, and recovery. The results revealed a significant reduction in SCL in biophilic environments (∆M = −0.38) compared to non-biophilic environments (∆M = −0.19). However, BP levels remained unaffected across both experiments. These findings suggest that biophilic design positively influences stress recovery and comfort, underscoring its potential in residential applications.